Enhancing Optical Distribution Point Placement: A Decision Support System Integrating Weighted Product Method, Content-Based Filtering, and Location-Based Services - Widiatry Widiatry; Viktor Handrianus Pranatawijaya; Dea Jeany Lestari (ITEGAM-JETIA)
The Optical Distribution Point (ODP) is a crucial element in fiber-optic internet networks, playing a key role in ensuring efficient service delivery. This study presents an integrated Decision Support System (DSS) that combines the Weighted Product Method (WPM), Content-Based Filtering (CBF), and Location-Based Services (LBS) to optimize ODP placement in urban areas. By considering multiple criteria such as ODP categories, customer preferences, and business types, the DSS provides a data-driven approach to strategic decision-making. The system’s ability to recommend ODPs based on customer needs, while visualizing key data through LBS, enhances the effectiveness of network expansion strategies. This comprehensive framework improves decision-making in urban internet services and offers a scalable solution for optimizing network infrastructure. The study demonstrates the potential of combining analytical models with user-focused technology to streamline service deployment and improve customer satisfaction.